2021
DOI: 10.1021/acs.langmuir.1c00779
|View full text |Cite
|
Sign up to set email alerts
|

Surface Topography Effects on Pool Boiling via Non-equilibrium Molecular Dynamics Simulations

Abstract: In this work, we investigate nucleate pool boiling via non-equilibrium molecular dynamics simulations. The effect of nano-structured surface topography on nucleation and transition to a film-like boiling regime is studied at the molecular scale, by varying the cavity aspect ratio, wall superheat, and wettability through a systematic parametric analysis conducted on a Lennard-Jones (LJ) system. The interplay of the aforementioned factors is rationalized by means of a classical nucleation theory-based model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The LJ potential provides an effective way to define the force field and capture the interatomic interactions within the system. [35][36][37] U = 4e ij…”
Section: Simulation Methodsmentioning
confidence: 99%
“…The LJ potential provides an effective way to define the force field and capture the interatomic interactions within the system. [35][36][37] U = 4e ij…”
Section: Simulation Methodsmentioning
confidence: 99%
“…However, some simulation method can analyze the effects of different wettability surfaces on bubble nucleation at a micro scale. Lavino et al (2021) showed bubble nucleation can occur even in narrow cavities on hydrophobic surface by non-equilibrium molecular dynamics simulation method. This also confirms the previous conclusion that bubble nucleation is more likely to occur on hydrophobic surfaces.…”
Section: Bubble Dynamics On the Homogeneous Wetting Surfacementioning
confidence: 99%
“…Boiling is as an exemplary illustration of a multiscale process. The sequence initiates with the heterogeneous nucleation of nanoscale bubbles due to molecular-level interactions between the fluid and the heated surface [1]. These bubbles undergo growth as the liquid transforms into vapor along the liquid-vapor interface.…”
Section: Introductionmentioning
confidence: 99%